Salinity Tolerance in Plants - Antonio Hernández Cortés, Jose (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Salt stress is one of the most damaging abiotic stresses because most crop plants are susceptible to salinity to different degrees. According to the FAO, about 800 million Has of land are affected by salinity worldwide. Unfortunately, this situation will worsen in the context of climate change, where there will be an overall increase in temperature and a decrease in average annual rainfall worldwide. This Special Issue presents different research works and reviews on the response of plants to salinity, focused from different points of view: physiological, biochemical, and molecular levels. Although an important part of the studies on the response to salinity have been carried out with Arabidopsis plants, the use of other species with agronomic interest is also notable, including woody plants. Most of the conducted studies in this Special Issue were focused on the identification and characterization of candidate genes for salt tolerance in higher plants. This identification would provide valuable information about the molecular and genetic mechanisms involved in the salt tolerance response, and it also supplies important resources to breeding programs for salt tolerance in plants.